IMPLEMENTING A NEW CURRICULUM WITH SPECIFIC REFERENCE TO HOME ECONOMICS IN PRIMARY SCHOOLS IN BINDURA DISTRICT IN ZIMBABWE - MUZENDA, DR. VERITY (IJRDO- Journal of Educational Research, 2017)
Home economics is a relatively new subject in Zimbabwe, having been introduced in the late1990s. Before then, most schools offered subjects like Carpentry for boys and Domestic Sciencefor girls. These subjects were taught by specialist teachers and as such, did not involve ordinaryclassroom practitioners. Home Economics seeks to develop in the youths an appreciation oftheir role in the solution of their own problems, and in the maintenance and upgrading of theirliving environment. Home Economics is aimed at promoting understanding of basic concepts ofnutrition, hygiene, clothing, consumerism and family life. Pupils in the end learn to cook, docraftwork, launder their clothes, clean the home environment, improve sanitation levels in theschool and community, plan their time and use it efficiently, budget their income, behave inacceptable ways, conserve resources and be good consumers. Important as Home Economicsmay appear to be particularly in the eyes of the policy makers, its introduction meant thatteachers taking junior classes found themselves teaching as many as eleven different subjects in asingle day. This may lead to an indifferent attitude among some teachers towards the newsubject and hence that the subject does not receive the attention and importance it deserves. Theintroduction of Home Economics in the primary system in Zimbabwe represents a change. Itssuccessful implementation will take time and move through a series of phases. It requireschanging teachers’ attitudes and feelings. It also requires that teachers’ capacities be built inorder to improve their mastery of the new content and teaching strategies. In the Zimbabweancontext, the school principal / head is at the centre of the implementation of all new curricula atschool level. In view of the above, this study sought to establish the support provided by schoolheads to teachers as they implement the Home Economics curriculum. The study employed thedescriptive survey method. The study was conducted in Bindura District in MashonalandCentral Province in Zimbabwe. Random sampling was used to come up with a sample of 59headmasters / mistresses from a total of 120 heads in the district, and 82 teachers from a total of2 000 teachers in the district. Data were collected by means of semi-structured questionnaire.The main findings revealed that principals had no clear vision of the new curriculum. There islittle effort put by principals towards the provision of resources, supervision of teachers isinadequate, there is no provision of technical assistance to teachers on the new curriculum.Heads, however, do make attempts to remove blockages which may inhibit the progress ofimplementation of the new curriculum. Based on the analysts of data, conclusions andrecommendations were made.